Analisis Laporan Keuangan sebagai Alat untuk Menilai Kinerja Keuangan Perusahaan pada PT Siloam International Hospitals Tbk Periode 2020-2023 - Aurelle Latisha Hardana; Dalizanolo Hulu (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the financial performance of PT Siloam International Hospitals Tbk during the period 2020–2023 using a financial ratio approach. The method employed is a descriptive quantitative analysis of liquidity ratios, capital structure and solvency, return on investment, operational performance, asset utilization, and market size. The results of this study indicate that the company's capital structure and solvency, return on investment, operational performance, and asset utilization ratios are in the very good category, while the liquidity and market size ratios are considered fairly good but not yet optimal. Overall, PT Siloam International Hospitals Tbk demonstrates solid, efficient, and sustainable financial performance, making it a commendable example of financial management excellence in the private hospital sector in Indonesia in the post-pandemic era.